Evaluating the mechanical and environmental impact of PEF plastic waste incorporated with graphene nano-platelets in concrete - Khan, Muhammad Basit; Najeh, Taoufik; Almujibah, Hamad; Al Zouabi, Mohammad Ghiath; Benjeddou, Omrane (Frontiers in Materials, 2024)
There has been a significant surge in the yearly use of plastics, leading to a notable rise.Consequently, the recycling of plastic garbage has emerged as a prominent concern around the world. This research explores the feasibility of using Polyethylene Furanoate (PEF) plastic waste as a substitute for coarse aggregate in concrete. The addition of Graphene Nano-platelets (GNPs) to the concrete mix was done with different quantities to improve its structural reliability. The research used an experimental research design in conducting its investigation. PEF waste plastic was added in concrete in varying proportions 0%, 5%, 15%, 20% and 25%, as a supplementary material to gravel and GNPs were added in different percentages 0%, 0.03%, 0.05%, 0.08% and 0.1% by weight of cement. Mechanical tests were conducted which includes compressive strength (CS), Split tensile strength (STS), Flexural strength (FS), Modulus of elasticity (MoE), Ultrasonic pulse velocity (UPV) and environmental assessment of concrete was done by assessing carbon in concrete and concrete's eco efficiency (ESE). It was found that 5% addition of PEF as substitute to coarse aggregate (CA) and 0.1% of GNPs gives optimum strength enhancing CS, STS, FS by 9.10%, 18.18% and 4.45% respectively. Response Surface Technique (RSM) models were created to provide mathematical equations for predicting predicted outcomes. All models were optimized using a multi-objective optimization approach, and then validated.